2021
DOI: 10.3390/biomedicines9091119
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Anti-Inflammatory Regulator Nrf2 Results in Breast Cancer Retardation In Vitro and In Vivo

Abstract: Nuclear factor erythroid-2 related factor-2 (Nrf2) is an oxidative stress-response transcriptional activator that promotes carcinogenesis through metabolic reprogramming, tumor promoting inflammation, and therapeutic resistance. However, the extension of Nrf2 expression and its involvement in regulation of breast cancer (BC) responses to chemotherapy remain largely unclear. This study determined the expression of Nrf2 in BC tissues (n = 46) and cell lines (MDA-MB-453, MCF-7, MDA-MB-231, MDA-MB-468) with divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 104 publications
1
34
0
Order By: Relevance
“…Further, the luciferase assay confirmed that Nrf2 is a target of miR-140-5p. Our results are in agreement with the previous findings showing increased expression of Nrf2 in BC cells [ 8 , 9 ]. These studies suggest that miR-140-5p might induce Nrf2 mRNA degradation and inhibit its translation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Further, the luciferase assay confirmed that Nrf2 is a target of miR-140-5p. Our results are in agreement with the previous findings showing increased expression of Nrf2 in BC cells [ 8 , 9 ]. These studies suggest that miR-140-5p might induce Nrf2 mRNA degradation and inhibit its translation.…”
Section: Discussionsupporting
confidence: 94%
“…Growing evidence also supports the role of Nrf2 in activating and maintaining the Hif-1α response as silencing Nrf2 reduces Hif-1α level [6,7]. In addition, a recent study showed elevated levels of Nrf2 in BC tissue and breast cancer stem cells, further confirming its cancer-promoting roles [8][9][10]. Thus, targeting Nrf2 could be a promising chemotherapeutic strategy for treating solid tumors.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, the study by Liang et al showed that Bru possessed its protective role in a rat model of oxygen-induced retinopathy of prematurity via counteracting microglial activation and cellular angiogenesis ( Liang and Wang, 2021 ). Inversely, a study showed that Bru could exert its inhibitory effect in breast cancer by stimulating lymphocyte migration towards tumor tissues and activating anti-tumor immune responses in vivo ( Bovilla et al, 2021 ). Obviously, this discrepancy can’t be briefly explained by Bru-dependent inhibition of Nrf2 and whether the inflammation-related effects also play important role in Bru treatment still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 pathway inhibition represents an attractive target for developing anticancer drugs ( 37 46 ) ( Table II ). The core results in Table II are summarized in illustrative Fig.…”
Section: Unique Redox Homeostasis In Cancermentioning
confidence: 99%
“…Nrf2 inhibitors specifically blocked the progression of Nrf2-positive cancers ( 39 ). Pharmacological inhibition and siRNA-induced downregulation of Nrf2 signaling in breast cancer cells resulted in sensitization of cancer cells to cisplatin ( 46 ). Nrf2 small-interfering RNA induces apoptosis and inhibits proliferation in various cancer cells ( 39 , 44 46 ).…”
Section: Unique Redox Homeostasis In Cancermentioning
confidence: 99%